Elemental analysis of aircraft engine smoke number filter samples with micro-PIXE. Issue 1 (1st October 2022) - Saitoh, K.; Fushimi, A.; Matsuyama, S.; Miwa, M.; Toyama, S.; Kikuchi, Y.; Durdina, L.; Anet, J.G.; Edebeli, J.; Spirig, C.; Takegawa, N.
Abstract: To extract information on elemental components and PM characteristics from smoke number (SN) filter paper, we were performed elemental analysis by micro-PIXE. As a result of elemental analysis of the SN filter, information on the elemental composition of jet engine exhaust PM was obtained. Regarding the SN filter, jet engine exhaust PM have been collected for each difference in engine thrust of various aircraft engines at aircraft turbine engines test cells around the world. By periodically analyzing the elemental composition of such the SN filter, it is possible to grasp the characteristics of the emission PM of each aircraft engine and the transformation of the elemental composition of the emission PM with the passage of time of the jet engine. This was thought to lead to the evaluation of jet engine.